Coxsackievirus B3 infection induces glycolysis to facilitate viral replication - Qian, Yujie; Yang, Yeyi; Qing, Wenxiang; Li, Chunyun; Kong, Min; Kang, Zhijuan; Zuo, Yuanbojiao; Wu, Jiping; Yu, Meng; Yang, Zuocheng (Frontiers in Microbiology, 2022)
Coxsackievirus B3 (CVB3) is a leading cause of viral myocarditis, but no effective treatment strategy against CVB3 is available. Viruses lack their own inherent metabolic system and instead depend on host cellular metabolism to its own benefit. In this study, we observed that CVB3 enhanced glycolysis in H9c2 rat cardiomyocytes and HL-1 mouse cardiomyocytes. Therefore, three key glycolytic enzymes, hexokinase 2 (HK2), muscle phosphofructokinase (PFKM), and pyruvate kinase M2 (PKM2), were measured in CVB3-infected H9c2 and HL-1 cells. Expression levels of HK2 and PFKM, but not PKM2, were increased in CVB3-infected H9c2 cells. And all three key glycolytic enzymes have elevated expression in CVB3-infected HL-1 cells. To further investigate this, we used 2 deoxyglucose, sodium citrate and shikonin as glycolysis inhibitors for HK2, PFKM and PKM2, respectively. Glycolysis inhibitors significantly reduced CVB3 replication while the glycolysis enhancer dramatically promoted it. In addition, glycolysis inhibitors decreased autophagy and accelerated autophagosome degradation. The autophagy inducer eliminated partial inhibition effects of glycolysis inhibitors on CVB3 replication. These results demonstrate that CVB3 infection enhances glycolysis and thus benefits viral replication.